Predictors of Knowledge, Attitudes, and Practices in Diabetic Kidney Disease Prevention Among Type 2 Diabetes Mellitus Patients in Northeast Peninsular Malaysia - Rosedi, Anas; Hairon, Suhaily Mohd; Yusoff, Siti Suhaila Mohd; Hameed, Anees Abdul; Basir, Mohammad Fazrul Mohammad (Jurnal Keperawatan Priority, 2025)
Diabetic kidney disease (DKD) is a significant complication among type 2 diabetes mellitus (T2DM) patients, impacting their quality of life and healthcare resources. This study aimed to assess the knowledge, attitudes, and practices (KAP) of DKD prevention and identify their predictors among T2DM patients in Northeast Peninsular Malaysia. A cross-sectional study involving 600 T2DM patients from government health clinics in Kelantan was conducted using a validated questionnaire. Logistic regression analyses were used to determine predictors of poor KAP. Results showed that 77% of participants had poor knowledge, 58.2% had poor attitudes, and 50.78% had poor practices regarding DKD prevention. Predictors of poor knowledge included being single, widowed, or divorced, lower education, and having at least one diabetic complication. Interestingly, unemployed participants had lower odds of poor knowledge. Poor attitudes were linked to lower education and unemployment, while poor practices were predicted by ethnicity, lower education, and poor attitudes. These findings suggest that DKD prevention strategies should focus on improving education, targeting vulnerable groups, and addressing socio-demographic factors to enhance KAP among T2DM patients.